2017
DOI: 10.1299/transjsme.16-00490
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective shape optimization for maximizing stiffness in thermo-elastic fields

Abstract: This paper presents a numerical solution to multi-objective shape optimization in order to achieve stiffness maximization in thermoelastic fields. Compliance evaluated by thermal deformation based on temperature distribution and by mechanical deformation based on surface force or body force is used as an objective functional by using weighting method.Shape gradient of the multi-objective shape problem is derived theoretically using the Lagrange multiplier method, adjoint variable method, and the formulae of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…However, since the purpose of this study is to maximize the stiffness, not the strength, it is unavoidable. In fact, the similar results can be seen in other studies (Azegami, 2020, Katamine andArai, 2017) on shape optimization for stiffness maximization based on minimizing mean compliance.…”
Section: Structure On Cavity Flowsupporting
confidence: 89%
See 1 more Smart Citation
“…However, since the purpose of this study is to maximize the stiffness, not the strength, it is unavoidable. In fact, the similar results can be seen in other studies (Azegami, 2020, Katamine andArai, 2017) on shape optimization for stiffness maximization based on minimizing mean compliance.…”
Section: Structure On Cavity Flowsupporting
confidence: 89%
“…On the other hand, the authors have proposed solutions to fundamental shape optimization problems for maximizing the stiffness of the linear thermoelastic bodies (Katamine and Arai, 2017) and for minimizing the dissipative energy in viscous flow fields (Katamine et al 2005), and demonstrated their validity. These solutions use the H 1 gradient method…”
Section: Introductionmentioning
confidence: 99%
“…The performance function shown in Eq. ( 1), which is expressed by the linear relaxation techniques that are often employed in multi-objective optimization, is used (Katamine and Arai, 2017;Mohamad et al, 2023). The performance function J is a performance index that weights the performance function J 1 to achieve minimal strain energy as shown in Eq.…”
Section: Topology Optimization For Multi-objective Optimization Problemsmentioning
confidence: 99%